Influence of Subjective and Objective Thermal Comfort Parameters on Building Primary Fuel Energy Consumption - I. Deshko, V.; A. Buyak, N.; O. Sukhodub, I. (International Journal of Engineering and Technology, 2018)
The building is considered together with a heating source in the analysis, it is also proposed to include a human thermal comfort model in this complex system. Regression equations for determining the comfortable room air temperature according to energy and exergy approaches are presented. Human thermal comfort model is included for the first time in the complex building energy system, by determining the comfortable room air temperature, which corresponds to PMV (predicted mean vote), not lower than value for the corresponding building category. The effect of enclosing structures thermal resistance changes on space average radiant temperature and on building category in terms of providing comfortable conditions is estimated. The influence of thermal comfort subjective parameters on primary fuel exergy consumption by the centralized heating system is estimated on the basis of developed model for the Ukrainian conditions.
Keywords: energy efficiency indicators; energy efficiency; exergy; heating; heat losses; human body exergy model; thermal comfort; primary fuel.